2019
DOI: 10.1186/s40249-019-0525-9
|View full text |Cite
|
Sign up to set email alerts
|

HIV prevalence in suspected Ebola cases during the 2014–2016 Ebola epidemic in Sierra Leone

Abstract: Background The 2014–2016 Ebola virus epidemic in West Africa was the largest outbreak of Ebola virus disease (EVD) in history. Clarifying the influence of other prevalent diseases such as human immunodeficiency virus infection and acquired immune deficiency syndrome (HIV/AIDS) will help improve treatment and supportive care of patients with EVD. Case presentation We examined HIV and hepatitis C virus (HCV) antibody prevalence among suspected EVD cases from the Sierra Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Recently, a study screening blood donor candidates for blood-borne pathogens found an HBsAg prevalence of 15% in men and 13% in women from a single hospital in Tonkolili Province, Sierra Leone. Data of the study conducted in the Tonkolili province on HCV showed a prevalence of 8% in men and 7% in women [16], of which 0.22% was suspected Ebola cases of the 2013-2016 outbreak [17]. These findings illustrate the serious public health risks that viral hepatitis pose in Sierra Leone.…”
Section: Introductionmentioning
confidence: 76%
“…Recently, a study screening blood donor candidates for blood-borne pathogens found an HBsAg prevalence of 15% in men and 13% in women from a single hospital in Tonkolili Province, Sierra Leone. Data of the study conducted in the Tonkolili province on HCV showed a prevalence of 8% in men and 7% in women [16], of which 0.22% was suspected Ebola cases of the 2013-2016 outbreak [17]. These findings illustrate the serious public health risks that viral hepatitis pose in Sierra Leone.…”
Section: Introductionmentioning
confidence: 76%
“…17 However, using ELISA, HCV antibodies were detected in 0.22% of samples of suspected Ebola cases during the 2014–2016 Ebola epidemic in Sierra Leone. 18 …”
Section: Resultsmentioning
confidence: 99%
“…17 However, HCV antibodies were detected in 0.22% of samples of suspected Ebola cases during the 2014–2016 Ebola epidemic in Sierra Leone. 18 This disparity in the prevalence of HBV and HCV among the various population groups indicates the need for a more structured study that will provide a solid definition of the prevalence of HBV and HCV among the general population of Sierra Leone.…”
Section: Discussionmentioning
confidence: 99%
“…The spread of the Ebola Virus Disease (EVD) has imposed a considerable challenge to public health systems and influenced the prevalence of other infectious diseases in affected countries [1]. Fruit bats have been identified as the main source of EVD which peaks periodically in West and Central African countries, especially during their migratory seasons.…”
Section: Introductionmentioning
confidence: 99%